Squamous cell papilloma a rare urinary bladder tumor, case report and operative video - Ahmed Mohamed (628889) (2022)
Bladder noninvasive squamous lesions are usually rare; here, we are presenting a case of 39 years old male patient with a benign squamous cell papilloma. The tumor grossly presented as cauliflower mass mimicking squamous cell carcinoma, while histologically, the tumor showed extensive keratinization at its surface and showed no nuclear atypia or stromal invasion. This tumor is benign and extremely rare. In this manuscript, we summarized a case of Squamous cell papilloma of the bladder with the first operative video for the transurethral resection of squamous cell papilloma with percutaneous management of associated urinary bladder stones. Other Information Published in: Urology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eucr.2022.102074